Improving The Accuracy of Smash Shots using Target Media - Rony Mohamad Rizal; Suhada Meirizal; Muhamad Rizwan Nuloh (Journal of Physical and Outdoor Education, 2026)
This research aims to determine the effect of using target media on improving the accuracy of badminton smash shots. Research method, the research method used is experimental. The research instrument used in this study employs a test of badminton smash accuracy based on predetermined movement mastery assessment criteria. The population used in this study consists of all the students at SMP Negeri 1 Cipatat who participate in the badminton extracurricular activities, totaling 18 people. The sample determination used the total sampling technique, meaning the sample was taken from the entire population, and the sample used in this study is the total number of students at SMP Negeri 1 Cipatat who participate in the badminton extracurricular activities, totaling 18 people. Based on the research results conducted by the author as well as the calculation and data analysis from the measurement results, the author can conclude as follows: The use of target media has a significant impact on the accuracy of smash shots in badminton at SMP Negeri 1 Cipatat. The average initial test result was 21.83, and the average final test result was 33.66. The t-test comparison result of the difference between the two test results was 11.53, which is greater than the t-table value of 1.74.